Chapter 9 REMOVING THE 'VEIL OF SECRECY' PUBLIC INQUIRIES AS SOURCES IN THE HISTORY OF PSYCHIATRY, 1960s-1970s - Hide, Louise (Taylor & Francis, 2022)
"Chapter 4: This chapter explores the ways historians can analyse museum collections to shed new light on psychiatric history. Focusing on the classic example of the straitjacket to illustrate the way psychiatric objects often function as symbols and practical items, it provides an introduction to material culture for the historian of psychiatry. First, it explores how and where we might find psychiatric objects, and how we can begin to analyse them. It examines what we can learn from observing the artefacts themselves, and what we might gain from placing them in the context of other sources. Reading objects alongside patient records, reports, publications, letters, and legal texts can shed new light on institutional life and practices. Objects may reveal the gap between rules and regulations and working practices and experiences within mental health care, and help to shed light on the hidden histories of psychiatric patients, especially women and working-class patients who were less likely to leave behind written accounts of their experiences. Finally, objects can help us as historians to confront our own assumptions. Acknowledging the symbolic meanings that historic items have often gained can help us to acknowledge the nuances of modern experiences of mental health care. Chapter 8: The disciplines of psychiatry and law are inextricably linked. Legal sources therefore provide invaluable material for understanding the history of psychiatry, but for historians unfamiliar with legal systems or legal history, there can be some barriers to their use. Focusing on the common law jurisdiction of England and Wales, this chapter describes three kinds of legal source - case law, court records, and legislation - and gives examples of the kind of information they contain, where they can be found, how they have been used by researchers, and what strategies can be applied to their interpretation. It concludes with an illustrative case study from the archives of the Court of Protection, and some final questions that these kinds of sources raise. Chapter 9: In the late 1960s, the first inquiries were held into claims of abuse and malpractice in certain NHS psychiatric and 'mental handicap' hospitals. As they continued through much of the 1970s, political indifference, failures in clinical leadership, poor management, and pernicious ingrained hospital cultures were revealed. Much of the vast repository of inquiry documentation that was generated at the time provides historians of today with immensely important insights into government interests, the impacts of NHS policy, and the cultural mechanisms that prevailed inside these large institutions. This article provides an overview of how the inquiries came about and were run, together with a summary of where to find sources today. It reflects on some of the epistemological and ethical questions that should be taken into account during the analysis and writing-up of the research, together with the potential challenges that come from working with such sensitive sources. Chapter 10: This chapter explores how our psychiatric histories can be enriched by engaging with the sources of mental health activism and the survivor movement. Beginning with a brief history of activism among patients and service users, it goes on to discuss the practical challenges associated with finding and working with a body of source material which is often ephemeral, uncatalogued, or hidden in private collections. While often difficult to access, activist materials can not only provide us with information on the history of the survivor movement, but open critical new perspectives on the wider history of psychiatry, and on the lives of service users past and present. The chapter concludes by reflecting on the historiographical and theoretical challenges which have been posed by mental health campaigners and survivor historians, to suggest how engaging with activist sources might change the ways we write the history of psychiatry. Chapter 13: Since the film camera was invented in the late nineteenth century, psychiatrists and their associates in allied disciplines have attempted to capture the symptomatology and treatment of mental illness in moving images. Film was used by 'psy' scientists for different ends over the course of the late nineteenth and twentieth century: as a diagnostic tool, as the means to create a visual archive of pathological gesture and expression, and as documentary and exposé. This chapter explores the opportunities and difficulties that face the historian of psychiatry when using film sources. It begins with a discussion of the parameters of psychiatric film and the expansion of its use in the mid-twentieth century. The following section explores the epistemological value of film within psychiatry and relevant implications for historical analysis. This extends into an examination of three salient issues facing the researcher: the fragmentary nature of film evidence, the ethical uncertainties surrounding the filming of patients, and the uses of empathy. The chapter ends with a list of major film archives and their holdings."